PENGAPLIKASIAN DOSIS PUPUK BOKASHI DAN KNO3 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) - Amiroh, Ana (Universitas Islam Darul Ulum, 2017)
Melon production produced by the farmer on average still low 105.29 tons/ha since the system has been champion by farmers is still traditional in nature. The purpose of this research is to know how much influence the fertilizer dosing KNO3 and bokashi towards growth and melon crops. This research was carried out in the village of Siser, Laren, Lamongan. Height of 8 m above sea level. This research method using Random Design Group (RAK) factorial, which consisted of two factors. Factor I namely Fertilizer Bokashi (B) include: B0 = control; B1 = 10 tonnes/ha; B2 = 20 ton/ha; B3 = 30 tons/ha. While the Factor II i.e. KNO3 (K) Fertilisers: K0 = control; K1 = 125 kg/ha; K2 = 150 kg/ha; K3 = 175 kg/ha. Conclusion of this research is to 1) there is a real difference in treatment doses of fertilizer bokashi on the plant and the number of variables of the leaf age 10, 15, 20, 25, 30, 35, 40 days after planting, the number of flower age 20, 25, 30 days after planting, fruit diameter at age 60 days after planting, weight of fruit at the age of 60 days after planting, weight brangkasan at age 60 days after planting; 2 KNO3 dosing treatment) on there is no real difference in all parameters and all age observations; 3) combination the best treatment at the treatment bokasi doses of 30 tons/ha and KNO3 dosing 175 kg/ha.